H2S in geothermal power plants: From waste to additional resource for energy and environment - Bassani A.; Previtali D.; Pirola C.; Bozzano G.; Nadezhdin I. S.; Goryunov A. G.; Manenti F. (Italian Association of Chemical Engineering (AIDIC), 2018)
Geothermal energy is a sustainable and clean energy source. Unfortunately, utilization of high-enthalpy geothermal systems is generally associated with emissions of gases like carbon dioxide (CO2), hydrogen sulfide (H2S), hydrogen (H2), nitrogen (N2), methane (CH4), and argon (Ar). The emission of some of these gases, particularly CO2, H2S and H2, is one of the main environmental concerns associated with the use of geothermal energy. The sequestration of these gases and their geological storage is the most diffuse viable option for reducing emissions. However, there is interesting technology, called AG2STM, that allows to convert H2S and CO2 into syngas. In this work, the match of this technology with geothermal power plant is analyzed as a new potential industrial route. The study is based on two different geothermal power plants located in Hellisheiði and Nesjavellirn (Iceland) that globally emit 61,800 t of CO2 and 28,200 t/y of H2S. The simulations provide some interesting results: (I) the total conversion of H2S that avoids its underground re-injection with the related environmental problem, (II) the reduction of CO2 emissions (about 8 %) and (III) the increasing of the global thermal energy produced with the same amount initial geothermal energy. The latter is due to the possibility to burn extra hydrogen coming from the AG2STM process. Finally, other advantages of this match are the production of an extra medium pressure steam and the possible reuse of the amount of H2 related to the geothermal plants emissions.